THE RELATIONSHIP BETWEEN BULLYING EXPERIENCES AND SELF-ACCEPTANCE ADAPTATION ABILITY IN ADOLESCENTS - Setiawan, Lilik; Eko Arik Susmiatin (Nursing Sciences Journal, 2025)
Incident bullying is an unwanted action that occurs in adolescents due to an imbalance of power, and bullying this has the potential to happen repeatedly and at any time. Experience bullying what the victim experiences directly will have an impact on their development and growth as a teenager, especially in terms of adaptability and social skills. Aggravating factors bullying namely lack of self- confidence, lack of self-acceptance, and lack of communication. This research aims to determine the relationship between experience bullying with the ability to adapt to self-acceptance. The design used in this research is correlation with the approach cross-sectional. The population of all students victims of bullying at Taruna Bakti Vocational School was 35 respondents. The sample in the research was 35 students obtained from engineering Total Sampling. Experience variable data bullying measured using a questionnaire The Olweus Bully and data on the variable ability to adapt to self-acceptance were measured using a questionnaire Berger’s Self Acceptance Scale, and data analysis with statistical tests Spearman rank. The research results stated that the majority of respondents 26 students (74.3%) experienced bullying lightweight with good acceptance criteria. The results of the analysis show that there is a relationship of experience bullying with the ability to adapt to self-acceptance (p-value 0.00<0.05). Good self-acceptance in individuals makes them able to develop themselves. able to interact with other people, and establish close relationships with other people without feeling disturbed by their weaknesses, because individuals who have high self-acceptance are aware of and accept all forms of shortcomings and weaknesses. the advantages that exist within him and realizing that other individuals also have these.